89Zr-atezolizumab imaging as a non-invasive approach to assess clinical response to PD-L1 blockade in cancer - Bensch, Frederike; Elly L van der Veen; Marjolijn N Lub-de Hooge; Jorritsma-Smit, Annelies; Boellaard, Ronald; Kok, Iris C; Oosting, Sjoukje F; Schröder, Carolina P; T Jeroen N Hiltermann; Anthonie J van der Wekken; Groen, Harry J M; Kwee, Thomas C; et al. (Nature medicine, 2018)
Programmed cell death protein-1/ligand-1 (PD-1/PD-L1) blockade is effective in a subset of patients with several tumor types, but predicting patient benefit using approved diagnostics is inexact, as some patients with PD-L1-negative tumors also show clinical benefit1,2. Moreover, all biopsy-based tests are subject to the errors and limitations of invasive tissue collection3–11. Preclinical studies of positron-emission tomography (PET) imaging with antibodies to PD-L1 suggested that this imaging method might be an approach to selecting patients12,13. Such a technique, however, requires substantial clinical development and validation. Here we present the initial results from a first-in-human study to assess the feasibility of imaging with zirconium-89-labeled atezolizumab (anti-PD-L1), including biodistribution, and secondly test its potential to predict response to PD-L1 blockade (ClinicalTrials.gov identifiers NCT02453984 and NCT02478099). We imaged 22 patients across three tumor types before the start of atezolizumab therapy. The PET signal, a function of tracer exposure and target expression, was high in lymphoid tissues and at sites of inflammation. In tumors, uptake was generally high but heterogeneous, varying within and among lesions, patients, and tumor types. Intriguingly, clinical responses in our patients were better correlated with pretreatment PET signal than with immunohistochemistry- or RNA-sequencing-based predictive biomarkers, encouraging further development of molecular PET imaging for assessment of PD-L1 status and clinical response prediction.